Effects of apple, orange and carrot pomace powders on gluten-free batter rheology and cake properties - Kirbas, Zahide; Kumcuoglu, Seher; Tavman, Sebnem (Springer Science and Business Media LLC, 2019)
This study examined the effects of using different fiber sources [apple pomace powder (APP), carrot pomace powder (CPP) and orange pomace powder (OPP)] on batter rheology and quality characteristics of rice flour-based gluten-free cakes. Gluten-free cake batters were formulated by replacing different amounts of rice flour (0, 5, 10, and 15%) with APP, CPP, and OPP. As a control cake, batters containing no pomace powder were used. The flow behaviors and viscoelastic characteristics of dietary fiber-enriched cake batters were investigated. All cake batters showed shear thinning behavior and the Power Law model was found to explain the flow behavior of all batter formulations. Apparent viscosity, elastic modulus (G'), and viscous modulus (G″) of the batter increased with increasing pomace powder content. Furthermore, addition of pomace powder increased batter specific gravity and crumb hardness, and decreased specific volume of cakes. Cakes containing 5% OPP had similar volume index and hardness values to the control sample. The sensory properties of the cake samples were investigated concerning color, texture, appearance, flavor and overall acceptability, and those with 5% OPP received the highest acceptance scores from the panelists.
Keywords: Batter; Gluten-free cake; Pomace; Fruits and vegetable by-products; Rheology; Dietary fiber